Conceptual Model of Enterprise Financial Management System with the Application of Modern Information Technologies - Yu. P. Kishkovich (Мир новой экономики)
In modern conditions of information technology development, the business management regime has changed. The sphere of management has expanded from internal to external. The innovation model of corporate Finance management must also adapt to this change. In an era of the global implementation of information systems and management tools, the innovation of the corporate financial management regime is not only in the rational planning and use of the company’s own resources but also in the inclusion of various categories of social resources necessary for the company’s operations in the category of corporate financial management and delivery to the enterprise. The purpose of the article is to consider the conceptual model of the financial management system of enterprises using modern information technologies. In the study, the author used a systematic approach to the enterprise’s financial management and methods of economic and deterministic factor analysis, synthesis, and grouping as well.